Angle Tracking Observer for Filtering Rotor Position Estimates in Sensorless Electric Drives - Jarzebowicz, Leszek; Cisek, Maciej; Opalinski, Artur (Elektronika ir Elektrotechnika, 2016)
Sensorless electric drives use measurements of electrical quantities to estimate rotor position and speed. Measurement errors deteriorate the estimation accuracy, thus additional means are necessary to remove high-frequency components from estimated signals. This paper proposes to use an Angle Tracking Observer (ATO) for reducing noise in rotor position estimates, which is related to random errors in the measurements. A simplified, universal structure of ATO has been designed for this purpose. Based on simulations, the gains of ATO algorithm have been selected for optimal balance between error components related to the measurement noise and to the filtering lag. Additionally, implementation issues have been discussed and laboratory validation has been carried out in the paper. The designed ATO is applicable to any sensorless drive and enables drive controller to substantially improve rotor estimation accuracy using very low computing overhead. DOI: http://dx.doi.org/10.5755/j01.eie.22.5.16341